PENCEGAHAN PENYAKIT PADA BUDIDAYA UDANG VANNAMEI (Litopenaeus vannamei) DI CV. AGRABINTA SHRIMP FARM DESA SINARLAUT KABUPATEN CIANJUR PROVINSI JAWA BARAT - afif12, farhan; Harijono, Teguh; Nazran, Nazran (Jurnal Perikanan Pantura (JPP), 2025)
Disease attacks are an important issue that should not be ignored as they relate to successful cultivation. Attacks can cause deaths and delays in the production process. To address this problem, disease prevention must be improved to reduce risk factors for production failure. Disease prevention in CV. Agrabinta Shrimp Farm includes prevention through the cultivation preparation stage, prevention through the selection and distribution of fry, prevention through the maintenance process, and prevention through water quality management and finally prevention through the implementation of biosecurity. This research was conducted for one month starting from January to February 2025. The fry used in this study are in plot 2 using PLB (Prima Larvae Bali) and plot 6 using STP fry (Suri Tani Pemuka) which is stocked in PL 10. The data taken from this study are prevention through cultivation preparation, selection and distribution of fry, maintenance, water quality management, and the application of biosecurity. It can be concluded that the implementation of biosecurity in CV. Agrabinta Shrimp Farm is good enough to keep shrimp from diseases and viruses that attack because both plots are still good and can survive until this research is completed. In plot 2, the growth is faster than in plot 6, this can also be seen from the sampling of Average Daily Growth (ADG) and Average Body Weight (ABW) which are always increasing, indicating that shrimp grow healthy because they are not affected by diseases or viruses.